IMPLEMENTATION OF POLICY ON EARLY MARRIAGE IN SUKABUMI CITY - Muhamad Feri Juliawan; Dian Purwanti; M. Rijal Amirulloh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Young marriages still occur a lot in urban areas, especially in Sukabumi City and are a threat to the young generation who will be the nation's future. The purpose of this study is to find out how the implementation of policies on special early marriages in the city of Sukabumi. This study uses a quantitative method with an analytical descriptive approach. The population in this study are teenagers in the city of Sukabumi. Researchers use Cluster Random Sampling. From the calculation results, a total sample of 100 adolescents in Sukabumi City was obtained. The data to be used in this study in terms of data sources are divided into two, namely secondary and primary data. Secondary data comes from related agency documents and literature studies. Meanwhile, the primary data was obtained from respondents, namely teenagers in the city of Sukabumi. Test the hypothesis in this study using a descriptive quantitative approach. Based on the results of the discussion and research described earlier, it can be concluded that the implementation of policies on special early marriages in Sukabumi City is included in the effective scale and classification, which is equal to 65.12%.